A formação do psicólogo do trânsito reflexões sobre a competência moral dos pós-graduandos - Bereta, Thaísa Angélica Déo da Silva (Editora Oficina Universitária, 2021)
This work addresses moral competence in the training of traffic psychologists and, for that, it highlights the importance of thinking about training that prioritizes reflective capacity, which integrates theoretical, technical and practical skills. Psychologist training to work in the traffic area should be based on knowledge of theories about human behavior in traffic, psychological assessment, legislation and even a practice that integrates the agent, the act and the result, as essential factors for an ethical and professional performance. However, for this to take shape, it is also essential to review the role of the educational institution in the development of morality and the use of more active teaching-learning methodologies.